2021
DOI: 10.1016/j.celrep.2021.109570
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of the second SARS-CoV-2 mRNA vaccine dose on T cell immunity in naive and COVID-19 recovered individuals

Abstract: The rapid development of mRNA-based vaccines against the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) led to the design of accelerated vaccination schedules that have been extremely effective in naïve individuals. While a two-dose immunization regimen with the BNT162b2 vaccine has been demonstrated to provide a 95% efficacy in naïve individuals, the effects of the second vaccine dose in individuals who have previously recovered from natural SARS-CoV-2 infection has not been investigated in deta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
48
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(61 citation statements)
references
References 17 publications
12
48
0
1
Order By: Relevance
“…Interestingly, SARS-CoV-2 naïve individuals and individuals with prior history of infection have distinct immune responses upon mRNA vaccination. Following the first vaccine dose, COVID-19 recovered individuals show significantly higher Sand RBD-specific IgG titers, superior serum neutralization activity (7,(12)(13)(14), and increased S protein-specific memory T and B cell responses than naïve individuals (4)(5)(6)15). This enhanced response is consistent with the persistence of humoral and cellular immunity against SARS-CoV-2 in convalescent individuals, as previously reported (16)(17)(18)(19)(20).…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…Interestingly, SARS-CoV-2 naïve individuals and individuals with prior history of infection have distinct immune responses upon mRNA vaccination. Following the first vaccine dose, COVID-19 recovered individuals show significantly higher Sand RBD-specific IgG titers, superior serum neutralization activity (7,(12)(13)(14), and increased S protein-specific memory T and B cell responses than naïve individuals (4)(5)(6)15). This enhanced response is consistent with the persistence of humoral and cellular immunity against SARS-CoV-2 in convalescent individuals, as previously reported (16)(17)(18)(19)(20).…”
Section: Introductionsupporting
confidence: 85%
“…Earlier phase III trials and more recent studies have demonstrated that mRNA-1273 vaccine induces a robust IgG response against SARS-CoV-2 wild type (WT) strain and promotes the generation of S-specific memory T and B cells after the two-dose regimen (2)(3)(4)(5)(6)(7)(8). Among the different antibodies induced by vaccination, those recognizing the S protein receptorbinding domain (RBD) are particularly relevant as they mirror the serum neutralizing capacity (9,10), and are considered a main correlate of immune protection and vaccine efficacy (11).…”
Section: Introductionmentioning
confidence: 99%
“…We observed that all convalescent individuals elicited a stronger humoral and cellular immunity than naïve individuals irrespective of the vaccination regime (Fig. 5A), in line with recent data (33)(34)(35).…”
Section: Characterization Of Spike-specific Humoral and Cellular Immune Responses In Vaccinated Sars-cov-2 Convalescentssupporting
confidence: 91%
“…We observed that all convalescent individuals elicited a stronger humoral and cellular immunity than naive individuals irrespective of the vaccination regime ( Figure 5 A), in line with recent data. 35 , 36 , 37
Figure 5 Spike-specific humoral and cellular immune response in convalescent vaccinated individuals Spike IgG antibody, sVNT, Spike-specific MBCs, and T cell responses were tested in five cohorts of naive vaccinated individuals: J (n = 12), J+J (n = 23), J+P (n = 9), P (n = 10), and P+P (n = 37). Same analysis was carried out in SARS-CoV-2 convalescent vaccinated individuals: J (n = 1), J+J (n = 5), P (n = 6), P+P (n = 7), and J+P (n = 5).
…”
Section: Resultsmentioning
confidence: 99%